Propuesta de implementación de un mecanismo de justificación para una correcta administración de la pensión alimenticia con el fin de hacer prevalecer los derechos del menor frente al derecho de alimentos en los casos en que sea administrada sin esmera diligencia - Márquez Delgado., Gabriela Arianna (2022)
The present research is entitled: "Proposal for the implementation of a justification mechanism for a correct administration of alimony in order to make the rights of the minor prevail over the right to food in cases in which it is administered without diligence". The present topic has two approaches, on the one hand, the right of children and adolescents to receive alimony and the need to implement a mechanism to justify alimony expenses for those cases in which alimony is being administered without the diligence that is due for other people's business in order to safeguard the right to alimony. The study carried out shows that there is a violation of rights due to the lack of a means to justify the expenses of alimony. The main objective of this research is to establish a mechanism for the justification of alimony by the legal representative or guardian of the minor for the correct administration of alimony. In the present investigation, materials and methods were used to develop the research, surveys and interviews were conducted with legal professionals and experts, thanks to which the results were used to analyze and propose the legal reform project to the Organic Code for Children and Adolescents in order to incorporate the figure of accountability with the purpose of protecting the rights of children and adolescents.